Tea detection based on YOLOv8 and PyQt5 - Yang, Tingting (International Journal of Advanced AI Applications, 2025)
Under the trend of intelligent transformation in modern agriculture, the contradiction between the efficiency and quality of tea picking urgently needs to be resolved. This study conducts tea detection optimization based on the YOLOv8 algorithm and constructs a complete technical path from theory to practice. The study first analyzes the network architecture of YOLOv8, combines the characteristics of the One-Stage algorithm, and clarifies its advantages in real-time tea detection. Through training and deployment on public datasets, the detection accuracy has been improved by 6.7% compared to the original YOLOv8, providing algorithmic support for mechanized picking. For the complex environment of tea gardens, a module optimization strategy is proposed: introducing a fusion attention module to generate a new C2fM module, and introducing asymmetric convolution to generate the ACBSPPF module. Through ablation experiments and cross-validation, the optimization effect was verified using mAP and FPS as indicators. The model has reached the industry-leading level in terms of real-time performance and accuracy. Research shows that the optimized YOLOv8 algorithm effectively solves the problem of tea detection. Finally, a tea detection system is designed using PyQt5, providing a feasible solution for the industrialization of intelligent picking technology.